Estrogen Enhances the Microvascular Reactivity Through RhoA-ROCK Pathway in Female Mice During Hemorrhagic Shock. Issue 4 (October 2021) - Yue, Yun-Xue; Zhai, Jia-Yi; Du, Hui-Bo; Jiang, Li-Na; Zhang, Li-Min; Wang, Chen; Zhao, Zhen-Ao; Zhang, Chun-Hui; Zhao, Zi-Gang
Abstract : ABSTRACT: Vascular hypo-reactivity plays a critical role inducing organ injury during hemorrhagic shock. 17β-estradiol (E2) can induce vasodilation to increase blood flow in various vascular beds. This study observed whether E2 can restore vascular hypo-reactivity induced by hemorrhagic shock, and whether E2 effects are associated with RhoA-Rho kinase (ROCK)-myosin light chain kinase phosphatase (MLCP) pathway. The hemorrhagic shock model (40 ± 2 mm Hg for 1 h, resuscitation for 4 h) was established in ovary intact sham operation (OVI), ovariectomized (OVX), and OVX plus E2 supplement female mice. Intestinal microvascular loop was used to assess blood flow in vivo, mRNA expression and vascular reactivity in vitro . Hemorrhagic shock significantly reduced norepinephrine microvascular reactivity. Decreased microvascular reactivity was exacerbated by OVX and reversed by E2 supplement. U-46619 (RhoA agonist) increased microvascular reactivity, and C3 transferase (an ADP ribosyl transferase that selectively induces RhoA ribosylation) or Y-27632 (ROCK inhibitor) inhibited sham mice microvascular reactivity. Similarly, U-46619 increased microvascular reactivity in OVI and OVX mice following hemorrhagic shock, which was abolished by Y-27632 or concomitant incubation of okadaic acid (OA) (MLCP inhibitor) and Y-27632. In OVX plus E2 supplement mice with hemorrhagic shock, Y-27632 inhibited microvascular reactivity, which was abolished by concomitant U-46619 application. Lastly, hemorrhagic shock remarkably decreased intestinal loop blood flow, RhoA and ROCK mRNA expressions in vascular tissues in OVX females, but not in OVI females, which were reversed by E2 supplement. These results indicate that estrogen improves microvascular reactivity during hemorrhagic shock, and RhoA-ROCK signaling pathway may mediate E2 effects. Abstract : Supplemental Digital Content is available in the text